2018
DOI: 10.1002/ejic.201801208
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Porphyrin Catalyzed Synthesis of Oxazolidin‐2‐ones by Cycloaddition of CO2 to Aziridines

Abstract: The reaction between N-substituted-2-arylaziridines and CO 2 is efficiently promoted by ruthenium(VI) imidoporphyrin complexes and yields a mixture of 5-aryl (A) and 4-aryl (B) substituted oxazolidin-2-ones with a regioisomeric A/B ratio up to 99:1. Several oxazolidin-2-one molecules were synthe- [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
5
19
0
Order By: Relevance
“…All the other starting materials were commercial products and used as received. Analytical data of cyclic carbonates 2, 6-12 [41,42] and oxazolidinone 13 [35] were in accordance with those reported in literature. NMR spectra were recorded at room temperature either on a Bruker Avance 300-DRX, operating at 300 MHz for 1 H and at 75 MHz for 13 C , or on a Bruker Avance 400-DRX spectrometers, operating at 400 MHz for 1 H and at 100 MHz for 13 C. Chemical shifts (ppm) are reported relative to TMS.…”
Section: Experimental Generalsupporting
confidence: 90%
See 4 more Smart Citations
“…All the other starting materials were commercial products and used as received. Analytical data of cyclic carbonates 2, 6-12 [41,42] and oxazolidinone 13 [35] were in accordance with those reported in literature. NMR spectra were recorded at room temperature either on a Bruker Avance 300-DRX, operating at 300 MHz for 1 H and at 75 MHz for 13 C , or on a Bruker Avance 400-DRX spectrometers, operating at 400 MHz for 1 H and at 100 MHz for 13 C. Chemical shifts (ppm) are reported relative to TMS.…”
Section: Experimental Generalsupporting
confidence: 90%
“…In our previously published paper on the CO 2 cycloaddition to aziridines catalysed by Ru(TPP)(NAr) 2 (1)/TBACl binary system, we reported the formation of the deactivated Ru(TPP)(NAr)(ArNCOO -TBA + ) complex (14) at the end of the catalytic reaction. [35] The formation of this latter complex indicated that the imido axial ligand on the ruthenium atom was able to interact with CO 2 thanks to the high electron density on the nitrogen atom, as already indicated by our previous DFT study. [36] The formation of complex 14 was also detected by ESI-MS at the end of the catalytic reaction forming cyclic carbonate 2.…”
Section: Insert Schemesupporting
confidence: 67%
See 3 more Smart Citations